Coupling a Stirling engine with a fluidized bed combustor for biomass. (20th July 2020) - Marra, Francesco Saverio; Miccio, Francesco; Solimene, Roberto; Chirone, Riccardo; Urciuolo, Massimo; Miccio, Michele
Summary: The paper deals with the integration between a kinematic Stirling engine and a fluidized bed combustor for micro‐scale cogeneration of renewable energy. A pilot‐scale facility integrating a 40 kWt combustor and a γ‐type Stirling engine (0.5 kWe ) was set up and tested to demonstrate the feasibility of this solution. The Stirling engine was installed at a lateral wall of the combustor in direct contact with the fluidized bed region. An experimental campaign was executed to assess the performance of the innovative integrated system. The experimental results can be summarized in: (a) very high combustion efficiency with biomass feeding, (b) elevated heat transfer rate to the engine, (c) a relatively small share (about 2 kWt ) transferred to the engine from the thermal power generated by the combustor (around 13 kWt ), (d) conversion to electric power close to the upper limit of the engine, (e) limited impact of the Stirling engine on the fluidized bed behavior, for example, temperature. From the analysis of measured variables, the dynamics is dominated by the fast response of the Stirling engine, which rapidly reacts to the slow changes of the fluidized bed combustor regime: the dynamic response of the tested facility as a thermal system was slow, the time constant being of the order of 10 minutes.